Displacement, Diversity, and Mobility: Career Impacts of Japanese American Internment - Jaime Arellano-Bover (Institute of Labor Economics (IZA), 2019)
One of the largest population displacement episodes in the U.S. took place in 1942, when over 110,000 persons of Japanese origin living on the West Coast were forcibly sent away to ten internment camps for one to three years. Having lost jobs and assets, after internment they had to reassess labor market and location choices. This paper studies how internees' careers were affected in the long run. Combining Census data, camp records, and survey data I develop a predictor of a person's internment status based on Census observables. Using a difference-in-differences framework I find that internment had a positive average effect on earnings in the long run. Chiefly due to strong pre- WWII anti-Asian discrimination, the comparison group is composed of non-interned Japanese and Chinese Americans. The evidence is consistent with mechanisms related to increased occupational and geographic mobility, possibly facilitated by the camps' high economic diversity. I find no evidence of other potential drivers such as increased labor supply, or changes in cultural preferences. These findings provide evidence of labor market frictions preventing people from accessing their most productive occupations and locations, and shed light on the resilience of internees who overcame a very adverse initial shock.
Keywords: J61; J62; N32; O15; 330; labor mobility; displacement; Japanese American Internment; WorldWar II; diversity